PEMBELAJARAN SOAL CERITA KPK DAN FPB DENGAN PENDEKATAN PROBLEM BASED LEARNING - nita, rasnita; Zainil, Melva; Harun, Mardiah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of this study is to describe the Improvement of Learning Outcomes about KPK and FPB story with approach of Problem Based Learning in Class IV SDN 29 Batang Anai Padang Pariaman. The approach used is qualitative approach and quantitative approach. Subject of this research is teacher and student of class IV consisting of 30 student. Student learning outcomes have increased with the average value of 69, 55% in the first cycle to 80.45% in cycle II. Thus, the Problem Based Learning approach can improve student learning outcomes.